Nudging and Crowdfunding Success : The Effect of Nudging on the Decision to Donate to a Sustainable Technology Project - Södergren, Alicia (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2023)
The overall aim of this thesis is to examine the factors that affect the decision to donateto a sustainable energy crowdfunding project, with particular emphasis on the role of socallednudging. The study examines the willingness to donate among of universitystudents at Luleå University of Technology. 412 surveys were distributed during lecturesto collect data regarding socio-economic characteristics, stated donation decisions withrespect to a hypothetical scenario involving the funding of a battery that stores renewableenergy, as well as attitudes. The theoretical framework mainly includes behaviouraleconomics, and two forms of nudging are tested in the survey through a split sampleapproach, namely psychological anchoring, and social nudging. The results show that thefactors that appear to have a positive influence on the individual's willingness to donateare the presence of psychological anchoring, a general interest in new technology, and aperceived individual responsibility for a sustainable future.